Giant Intra-Abdominal Desmoid Tumor in a Young Male without History of Surgery, Trauma, or Familial Adenomatous Polyposis - Noritoshi Mizuta; Kozo Tsunemi (Case Reports in Surgery)
Desmoid tumors are rare, monoclonal myofibroblastic neoplasms that occur in the extremities, the trunk, and the abdominal cavity. We present a case that is significant for its rarity and for consideration of its treatment plan. A 17-year-old male reported swelling of his abdomen and abdominal pain. He was referred to our hospital with no history of surgery, trauma, or familial adenomatous polyposis. A large tumor in the abdominal cavity was detected by computed tomography, and surgical resection was performed. The tumor was thought to have developed from the anterior lobe of the transverse colon mesentery. It weighed 5.9 kg. Tumor cells with collagen fibers were observed in histopathological examination, but heteromorphism and the nuclear fission image were not apparent. Immunostaining revealed beta-catenin expression in the tumor cell nucleus. Diagnosis was an intra-abdominal desmoid tumor. Currently, there are no signs of recurrence. In this case, preoperative diagnosis was difficult, but surgery was the optimal treatment according to the symptoms. Desmoid tumors have invasive development and common local recurrence, so sufficient range of resection including normal tissue and strict follow-up are necessary.